Specific Features of the Image of Alexander the Great in Burgundian Art in the Middle and Second Half of the 15th Century - Saltykova, Veronika A. (Actual Problems of Theory and History of Art, 2025)
The article examines a number of illustrated manuscripts and tapestries depicting the history of Alexander the Great, commissioned by the Burgundian dukes, Philip the Good and Charles the Bold. The author analyzes the iconographic features of the images depicting Alexander in close relation to the textual sources, such as ‘Facts and Conquests of Alexander’ by Jean Wauquelin and the French translation of Quintus Curtius Rufus’s ‘The History of Alexander the Great’, executed by Vasco de Lucena. The study of these texts and the related artworks revealed the key changes that took place in the perception of Alexander during the middle and second half of the 15th century, when there was a period of a grandiose Transalpine art transformation. Previously, Alexander was represented more as an adventurer and a courtly knight, but then, he began to resemble a generous and wise ruler. The article also discusses the impact of humanistic literature on the depiction of Alexander the Great. Petrarch and Boccaccio gave a sharply critical assessment of his actions, which led to a more complex portrayal of his character. The ambivalent nature of Alexander’s personality — a combination of virtue and pragmatism — made him an attractive role model for the Burgundian rulers. Using works of art and visual propaganda, the dukes actively engaged the figure of Alexander to construct an image of their own power and political aspirations. The analysis of the textual and visual sources in the article clearly demonstrates a gradual shift from the medieval interpretation of Alexander the Great to the Renaissance image concept.